2014
DOI: 10.5455/jcer.201422
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial drug utilization pattern in neonatal sepsis in a tertiary care hospital

Abstract: Objective: The objective of this study was to determine antimicrobial drug use in newborns at a tertiary care neonatal intensive care unit, to identify educational/research priorities in neonatal drug therapy. Materials and Methods: This prospective observational study included 713 patients of neonatal sepsis over a period of 18 months. Data like name, age, sex, birth weight, gestational age, antibiotics used were recorded in the previously prepared case record form. Results: Number of patients admitted in ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
2
2
1
Order By: Relevance
“…Comparatively, the mean duration of stay on admission in this study (3.6 ± 4.8 days) was lower than the earlier mean duration of stay of 7.6 ± 5.7 days on admission reported by Vaniya et al 26 However, other authors have reported a mean duration of stay as high as 22 days. 27 Neonatal sepsis is considered a clinical emergency, with its management having an implication for the neonate’s lifelong survival.…”
Section: Discussioncontrasting
confidence: 92%
“…Comparatively, the mean duration of stay on admission in this study (3.6 ± 4.8 days) was lower than the earlier mean duration of stay of 7.6 ± 5.7 days on admission reported by Vaniya et al 26 However, other authors have reported a mean duration of stay as high as 22 days. 27 Neonatal sepsis is considered a clinical emergency, with its management having an implication for the neonate’s lifelong survival.…”
Section: Discussioncontrasting
confidence: 92%
“…In this study, the mean duration of stay on admission was lower than the earlier mean duration of stay reported by Vaniya et al 37 Other authors have reported a mean duration of stay as high as 22 days. 38 Neonatal sepsis is considered a clinical emergency, with its management implying the neonate's lifelong survival.…”
Section: Discussioncontrasting
confidence: 80%
“…Обсуждение дополнительных результатов исследования В целом, большинство исследований из различных регионов мира свидетельствует, что в ОРИТ новорожден-ных антибиотики получают до 100% пациентов (особенно глубоконедоношенных) [15][16][17], что показано и в нашем исследовании. В международной практике антибактери-альной терапии одной из основных тенденций является также стремление к сокращению объема потребления [19].…”
Section: резюме основного результата исследованияunclassified